The Influence of Victim Vulnerability and Gender on Police Officers’ Assessment of Intimate Partner Violence Risk - Storey, Jennifer E. (J Fam Violence, 2016)
This study investigated the influence of victim vulnerability factors and gender on risk assessment for intimate partner violence (IPV). 867 cases of male and female perpetrated IPV investigated by Swedish police officers using the Brief Spousal Assault Form for the Evaluation of Risk (B-SAFER) were examined. For male-to-female IPV, victim vulnerability factors were associated with summary risk judgments and risk management recommendations. For female-to-male IPV, vulnerability factors were more often omitted, and consistent associations were not found between vulnerability factors, summary risk judgments, and risk management. Results indicate that B-SAFER victim vulnerability factors can assist in assessing male-to-female IPV risk. Further research is necessary to examine the use of B-SAFER victim vulnerability factors for female-to-male IPV, as results showed victim vulnerability factors to be less relevant to officers’ decision making, particularly their management recommendations. However, several variables external to the B-SAFER, such as the availability of management strategies may account for these findings.